Let’s Focus In: A Guide to Eye Tracking Technology in Agricultural Communications Research - Caitlin Anne Stanton; Laura Morgan Fischer (Journal of Applied Communications, 2020)
Communicating with the public about the agricultural industry often presents challenges in learning how to convey messages that are deemed as salient to various types of people. Media is understood through complex cognitive processes that result in varying attitudes throughout interaction with a stimulus, thus requiring methods that go beyond traditional self-report measures. The majority of agricultural communication research has encompassed quantitative and qualitative research, which often does not account for changes throughout media consumption. Eye tracking is an underutilized resource in agricultural communication that can be used to yield further insight into areas of interest that elicit visual attention and can signal further processing of information. This professional development paper examines the contributions of eye tracking research in agricultural communication and provides an overview of strategies for implementation in both research and practice.
Keywords: Eye Tracking; Visual Attention Allocation; Research Methods